The impact of varicella vaccination: A 2005-2019 interrupted time series analysis - Katherina U. Miranda; Rodrigo DeAntonio; Ximena Norero; Dora Estripeaut (Taylor & Francis Group, 2023)
ABSTRACTVaricella is an acute, highly contagious disease in susceptible individuals and is preventable through vaccination. This study aimed to determine the impact of varicella vaccination on hospitalizations and complications at a pediatric reference hospital in Panama before and after the vaccine introduction. This descriptive ecological study analyzed clinical records of patients diagnosed with varicella through a retrospective and interrupted time series analysis. An autoregressive integrated moving average model was built to compare the incidence rates observed after vaccination with those expected rates derived from the model. A statistical model was fitted to the observed interrupted time series data by regression and used to predict future trends. The mean difference in varicella hospital discharges before and after the introduction of the varicella vaccine was 47%. The rate of hospitalizations for varicella decreased to 52.3%. A declining trend in varicella hospitalizations was observed from 2015 after vaccine introduction in 2014. Complications in vaccinated patients were secondary skin and soft tissue infection, possibly due to bacterial superinfection. The impact of varicella vaccination on reducing varicella hospital discharges reported at a pediatric reference hospital in Panama was confirmed.